2022
DOI: 10.1155/2022/1698842
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation of the Effect of Oral Implant Surgery on Clinical Treatment and Oral Function of Patients with Dentition Loss

Abstract: In order to investigate the effect of oral implant surgery on clinical treatment and oral function of patients with dentition loss, a total of 118 patients with dentition loss in the Department of Stomatology of our hospital from January 2019 to January 2022 are retrospectively analyzed. They are randomly divided into the conventional group and the implant group. The conventional group is treated with conventional dentition restoration, and the implant group is treated with oral implant restoration. The repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%